Following acute encephalitis, Semliki Forest virus is undetectable in the brain by infectivity assays but functional virus RNA capable of generating infectious virus persists for life - Fragkoudis, Rennos; Dixon-Ballany, Catherine; Zagrajek, Adrian; Kedzierski, Lukasz; Fazakerley, John (MDPI, 2018)
Alphaviruses are mosquito-transmitted RNA viruses which generally cause acute disease including mild febrile illness, rash, arthralgia, myalgia and more severely, encephalitis. In the mouse, peripheral infection with Semliki Forest virus (SFV) results in encephalitis. With non-virulent strains, infectious virus is detectable in the brain, by standard infectivity assays, for around ten days. As we have shown previously, in severe combined immunodeficient (SCID) mice, infectious virus is detectable for months in the brain. Here we show that in MHC-II-/- mice, with no functional CD4 T-cells, infectious virus is also detectable in the brain for long periods. In contrast, in the brains of CD8-/- mice, virus RNA persists but infectious virus is not detectable. In SCID mice infected with SFV, repeated intraperitoneal administration of anti-SFV immune serum rapidly reduced the titer of infectious virus in the brain to undetectable, however virus RNA persisted. Repeated intraperitoneal passive transfer of immune serum resulted in maintenance of brain virus RNA, with no detectable infectious virus, for several weeks. When passive antibody transfer was stopped, antibody levels declined and infectious virus was again detectable in the brain. In aged immunocompetent mice, previously infected with SFV, immunosuppression of antibody responses many months after initial infection also resulted in renewed ability to detect infectious virus in the brain. In summary, antiviral antibodies control and determine whether infectious virus is detectable in the brain but immune responses cannot clear this infection from the brain. Functional virus RNA capable of generating infectious virus persists and if antibody levels decline, infectious virus is again detectable.